Unravelling the ecological complexity of soil viromes: Challenges and opportunities - Bi, Li; Yu, Dan-Ting; Han, Li-Li; Du, Shuai; Yuan, Cheng-Yu; He, Ji-Zheng; Hu, Hang-Wei (The Science of the total environment, 2022)
Viruses are extremely abundant and ubiquitous in soil, and significantly contribute to various terrestrial ecosystem processes such as biogeochemical nutrient cycling, microbiome regulation and community assembly, and host evolutionary dynamics. Despite their numerous dominance and functional importance, understanding soil viral ecology is a formidable challenge, because of the technological challenges to characterize the abundance, diversity and community compositions of viruses, and their interactions with other organisms in the complex soil environment. Viruses may engage in a myriad of biological interactions within soil food webs across a broad range of spatiotemporal scales and are exposed to various biotic and abiotic disturbances. Current studies on the soil viromes, however, often describe the complexity of their tremendous diversity, but lack of exploring their potential ecological roles. In this article, we summarized the major methods to decipher the ecology of soil viruses, discussed biotic and abiotic factors and global change factors that shape the diversity and composition of soil viromes, and the ecological roles of soil viruses. We also proposed a new framework to understand the ecological complexity of viruses from micro to macro ecosystem scales and to predict and unravel their activities in terrestrial ecosystems. [Display omitted] •We summarized the most recent progress made in soil viral ecology.•The major experimental and computational approaches to study soil viromes were reviewed.•Abiotic and biotic factors and global changes co-influence soil viral communities.•We highlighted the key potential ecological roles of viruses in soil.•We propose a framework to unravel the ecological complexity of viruses in soil.